Global Energy Statistics & Managing the Global Expansion of Nuclear Energy - Wilson, Paul P.H. (My University, 2009)
Promega's 8th Annual International Bioethics Forum followed the theme of sustainability and included a panel on energy sustainability with Paul Wilson, Tracey Holloway, and Greg Nemet. This presentation includes a few slides from the opening that set the stage with some global energy statistics, and then has a few slides that raise issues and solutions for managing the expansion of nuclear energy around the globe.
Keywords: policy; nuclear energy; energy statistics